Clinical, radiological and histological correlation in diagnosis of orbital tumours - Ralene Sim; Stephanie Ming Young; Rupesh Agrawal; Gangadhara Sundar (Cogent Medicine, 2019)
This is a 10-year retrospective review to correlate clinical features, imaging and pathologic findings in lesions of the orbit in order for a more accurate diagnosis. Eighty-three patients undergoing biopsy or orbitotomy between September 2000 and August 2010 for orbital lesions were evaluated clinically, radiologically (CT) and histopathologically to determine the correlation between the three modalities. There was complete correlation for all cases under congenital orbital tumours and lacrimal gland and sac tumours that were studied. Negative correlation between clinical diagnosis and final histopathology was seen most significantly in lymphoproliferative disorders and orbital inflammation. The most commonly misdiagnosed type of orbital lesion is lymphoproliferative disorder and orbital inflammation, whereas the least commonly misdiagnosed type of orbital lesion is congenital and lacrimal gland and sac tumours. There was significant disparity between clinical diagnosis and radiology report, however, relatively less disparity between histopathology report and clinical diagnosis.